MEDIATING ROLE OF POSTPARTUM DEPRESSION BETWEEN PERCEIVED SPOUSAL SUPPORT AND POSTPARTUM MATERNAL BONDING - Adil, Adnan; Shahbaz, Rabia; Khan, Anam; Ameer, Sadaf (Journal of Ayub Medical College Abbottabad, 2021)
Background: The present study intended to examine the direct effects of perceived spousal support and postpartum depression on postpartum maternal bonding. Furthermore, it also explored the mediating role of postpartum depression between perceived spousal support and postpartum maternal bonding. Methods: This study was based on a cross-sectional survey research design. A purposive sample of 170 women who were already diagnosed by the doctor/psychiatrist as suffering from postpartum depression was recruited from different hospitals of Gujrat district. Urdu translated versions of The Marital Empathy Scale, Postpartum Bonding Questionnaire, and the Edinburgh Postnatal Depression Scale were used to measure the focal constructs of the study. Results: IBM Amos was used to test the proposed model of the present study. Path analysis revealed that perceived spousal support had negative significant direct effects on postpartum depression and postpartum maternal bonding. Postpartum depression had significant positive direct effect on postpartum maternal bonding. Finally, the significant indirect effect of perceived spousal support through postpartum depression on postpartum maternal bonding was negative. Conclusion: The mediation found in the present study suggested that perceived spousal support reduced the postpartum depression, which in turn, lowered the chances of dysfunctional postpartum maternal bonding with the baby. Implications of the study along with the recommendations for future studies have been reflected upon. Keywords: Postpartum depression; postpartum maternal bonding; perceived spousal support